تدريس الحوار والأديان ضمن مادة التربية الإسلامية - علي زلماط .; د.فؤاد الغزيزر . (TAWASUT, 2022)
ملخص:يهدف هذا البحث إلى الوقوف على أهمية مادة التربية الإسلامية في تدريس الحوار، بالمملكة المغربية، من خلال المنهاج المؤطر والمقررات الدراسية، وذلك باستقراء الدروس والنصوص التي تدعو إلى الحوار. ويأتي هذا البحث أيضا للدعوة إلى تدريس مادة دراسة الأديان أو علم الأديان بالتعليم الثانوي ضمن مادة التربية الإسلامية، لما لها من أهمية في بناء النظام الدفاعي العقائدي للفرد تجاه الأفكار الدينية الوافدة عليه، وتكوين شخصية المتعلم على حسن التواصل والتفاعل مع الآخر البعيد.الكلمات المفتاحية: الحوار – الأديان – التربية الإسلامية – التدريس – المنهاج. Abstract:This research aims to identify the importance of the subject of Islamic education in teaching dialogue, in Moroccan kingdom, from the courses of all levels, and the framed curriculum, by extrapolating lessons and texts that invite dialogue. This research also comes as an invitation to teach the subject of the study of religions or the science of religions in secondary education within the subject of Islamic education. Because of its importance in building the individual’s doctrinal defense system against the religious ideas that come to him, and the formation of the learner's personality on good communication and interaction with the distant other.Keywords: Dialogue - Religions - Islamic Education - Teaching - Curriculum.